Feto-Maternal Outcomes in Pregnancy with Fibroids - Sadaf Shafique; Nadeem Ibrahim; Umbreen Akram; Erum Pervaiz; Tahira Riaz; Zahra Waseem (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To determine the fetal and maternal outcomes of pregnancy with fibroids. METHODOLOGY: This prospective, case-series study was conducted at the Department of Obstetrics and Gynaecology, CMH Gujranwala, Pakistan, from July 2023 to June 2024. Females aged between 20-35 years, with singleton pregnancy, planned to undergo delivery with a diagnosis of single or multiple fibroids were analyzed. Maternal effects like pressure symptoms, urinary retention, abdominal pain, preterm delivery, and postpartum hemorrhage were noted. Fetal outcomes included miscarriage, oligohydramnios, intrauterine growth retardation, and abnormal presentation. RESULTS: In a total of 81 women, the mean age was 26.22±3.56 years. The number of fibroids was 1, 2, 3, and more than 3 in 24 (29.6%), 23 (28.4%), 19 (23.5%), and 15 (18.5%) women, respectively. Fibroid size ranged from 3 to 5 cm in 45 (55.6%) women, while intramural fibroids were the most common type, noted in 51 (63.0%) women. The fibroids were located of the anterior wall in 38 (46.9%) women. Pressure-related symptoms were the most frequent types of complaints reported by 67(82.7%) women in pregnancy with fibroids. Oligohydramnios was found in 18(22.2%) babies, whereas intrauterine growth retardation was observed in 17(21.0%). 25 (31.6%) babies were born preterm. Malpresentation was observed in 29(35.8%) cases. CONCLUSION: Intramural fibroids were the most common type of fibroids in pregnancy, while the anterior wall was the most common location. Pressure-related symptoms were the most frequent complaints in pregnancy with fibroids. Nearly one-third of the newborns are at risk of preterm birth or malpresentation.